TOURISM LEAKAGE OF THE ACCOMMODATION SECTOR IN BALI - Oka Suryawardani, I G. A.; Gde Bendesa, I Komang; Antara, Made; Suryawan Wiranatha, Agung (ITB Journal Publisher, LPPM ITB, 2014)
Tourism has been a driving force of economic development and has become the leading economic sector in Bali Province. However, the economic impacts of tourism development have not been fully beneficial for the Balinese community. Tourists’ expenditure has not been totally remaining in Bali’s economy. Some of the expenditures by tourists leak out of the destination, called tourism leakage, in the form of payments for imported products and services, payment of wages for foreign employees, and profits transferred to foreign owners. So far, the amount of tourism leakage in Bali has not been calculated. Therefore, there is a need to ascertain the current amount of leakage in Bali tourism. This paper estimates the amount of tourism leakage from the accommodation sector in Bali through a micro analysis at the industrial level. There were 79 hotels selected as a sample based upon a purposive probability to size sampling method in four main tourist destinations in Bali, namely Kuta, Nusa Dua, Sanur and Ubud. Four types of accommodation were considered in estimating tourism leakage. The results showed that the highest percentage of leakage was in the 4 & 5 Star-rated chain hotels, i.e. 51.0 % of total revenue. It was followed by the 4 & 5 Star-rated non-chain hotels (22.7 %), and 1, 2 & 3 Star-rated hotels (12.0 %). Meanwhile, the lowest leakage was on the Non star-rated hotels (8.8 %). Overall, the average tourism leakage on accommodation sector in Bali was 18.8 %. These results indicate that (i) the higher the level of hotel classifications, the more leakage will be; and (ii) accommodation which was owned by a foreigner and/or managed by an international chain had more leakage than other types of accommodation. The more leakage, therefore the less revenue from tourism will be directly received by hotel and undirectly by the local community as tourism is the main source of economic development of Bali Province.